Retinal Changes in Transgenic Mouse Models of Alzheimer’s Disease - Guo, Li; Ravindran, Nivedita; Shamsher, Ehtesham; Hill, Daniel; Cordeiro, M. F. (Current Alzheimer Research, 2021)
Alzheimer’s disease (AD) is a neurodegenerative disorder, the most common form of dementia. AD is characterised by amyloid-β (Aβ) plaques and neurofibrillary tangles (NFT) in the brain, in association with neuronal loss and synaptic failure, causing cognitive deficits. Accurate and early diagnosis is currently unavailable in lifespan, hampering early intervention of potential new treatments. Visual deficits have been well documented in AD patients, and the pathological changes identified in the brain are also believed to be found in the retina, an integral part of the central nervous system. Retinal changes can be detected by real-time non-invasive imaging, due to the transparent nature of the ocular media, potentially allowing an earlier diagnosis as well as monitoring disease progression and treatment outcome. Animal models are essential for AD research, and this review has a focus on retinal changes in various transgenic AD mouse models with retinal imaging and immunohistochemical analysis as well as therapeutic effects in those models. We also discuss the limitations of transgenic AD models in clinical translations.
Keywords: treatment